Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan - Laksmi Kusumawardani, (Bisnis dan Manajemen, 2010)
The study is intented to measure the associative type of organizational culture on the performance of employees in Auto 2000 Surabaya. Indicators of organizational culture in this research referred to innovation, integration, leadership behavior, stability and orientation details. Collecting data using a questionnaire to 50 employee of Auto 200 Surabaya. To analyze the data in this research using multiple linear regression. That form of analysis is to determine the level of influence and cultural organizations contributions to job performance in that organizations